(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the didactic possibilities and methodological solutions of using digital pedagogical technologies in teaching chemistry. Digital tools are justified as an effective mechanism for visualizing chemical concepts, modeling complex processes, enhancing preparation for laboratory work, and promptly monitoring learning outcomes. Through virtual laboratories, simulations, LMS platforms, digital testing and formative assessment tools, students are shown ways to develop critical thinking, scientific interpretation, experimental safety, and data handling skills in addition to subject competencies. It also shows the conditions for integrating digital technologies with lesson design, interactive methods, and real laboratory practice, as well as limitations in practical implementation.